As decisões da Justiça desportiva e o seu cumprimento - Dib, Luís Felipe Ferreira (2018)
With the 1988 Federal Constitution, sport was allocated to constitutional levels, recognizing it’s political, economic, cultural, social, educational and, above all, legal relevance. Thus, the constituent legislator reserved a specific section for sport, notably, the article 217 of CF88, recognizing its inseparable character of life. This article demonstrates, in the words of Professor Álvaro Melo Filho, that "(sports law) is not a disposable right", so much that "healthy and endowed with depth and institutional breadth, serving as beacon or cornerstone of the jus-sport pyramid with its complexities, variations and specificities. " In dealing with the Brazilian Sport Court, the first and second paragraphs (§ 1 and 2) of art. 217, providing for the Brazilian Sport Court formulated as a single jurisdictional presupposition inserted in the bulge of the Constitution of the Federative Republic of Brazil. It is important to point out that the Brazilian Courts of Sport are essentially sui generis, without any reference in previous jurisdictions. In this context, the purpose of this study is to discuss the effectiveness of sports law in the area of the effectiveness of judgments rendered in the field of sporting justice and what mechanisms in our legal system may be adopted to guarantee their execution